“TAG” TEMAN DAN #HASTAG REKONSEPSI INTERAKSI SOSIAL DI PLATFORM INSTAGRAM - Mita Rosaliza; Raja Syamsidar; Hesti Asriwandari (Universitas Lancang Kuning, 2022)
Tag a friend in the comments column on the Instagram platform is one mechanism to start interacting between users on social media. Is it possible to just